Psychological and neuro-morphological predictors of resilience in healthy adults: the whole is more than the sum of its parts - Carlo Fabrizio; Eleonora Picerni; Daniela Laricchiuta; Davide Decandia; Davide Decandia; Fabrizio Piras; Andrea Termine; Gianfranco Spalletta; Laura Petrosini; Debora Cutuli; Debora Cutuli (Frontiers in Neuroscience)
IntroductionResearch in resilience has shifted the focal point from a pathological orientation (responses to recovery from trauma or stress) to an emphasis on the role of resilience in health (protective factors to maintain health levels despite eventual adversities). Even if many single factors impact resilience capacities, an integrative predictive model including psychological constructs, personality traits, and brain structural features may offer a more profound knowledge of trait resilience.MethodsWe examined the associations between Resilience Scale-10 scores with numerous psychological dimensions, personality traits, and neuro-morphological features (brain volumes and thickness) in 69 healthy adults of both sexes. Furthermore, we investigated the predictors potentially associated with resilience by regression modeling.ResultsIn the present exploratory study resilience values were predicted: positively by some personality characteristics (Conscientiousness, Openness, Resourcefulness, Enlightened second nature), psychological dimensions (Self-efficacy, Positive affect, Confidence), and brain morphological aspects (volumes of amygdala and hippocampus, and cortical thickness of temporal pole); and negatively by other personality traits (Fear of uncertainty) and psychological dimensions (Anxiety, Depression, Need for Approval).DiscussionThe present results, although exploratory and hypothesis-generating rather than confirmatory, suggest that the identification of the multiple psychological and personality features and neuro-morphological aspects associated with resilience may represent a good step forward in understanding the factors that predispose individuals to be resilient.